BETWEEN ARCHAEOLOGY AND METAL DETECTING, ANCIENT COINS FROM OCNIȚA-BURIDAVA - Silviu I. PURECE (Journal of Ancient History and Archaeology)
The intensification of discoveries made with metal detectors and, consequently, the appearance of an increasing number of coins without being associated with a very precise location, although many seem to originate from archaeological contexts, creates difficulties in the recovery of historical information. Associating discoveries from metal detection with information related to findings with a clear archaeological context can be a solution in understanding certain phenomena that led to their deposition, loss, or concealment. Unfortunately, however, we do not always have clear numismatic and archaeological information, not even for those derived from older systematic research. Additionally, coins are often hard to locate in museum collections due to the challenges that collections have faced over time. Our initiative aims to recover and reconstruct, as much as possible, the numismatic information, localization, and context of monetary discoveries from Ocnița-Buridava. We also aim to integrate, as much as possible, the context of findings made in the region through metal detection. We believe that in this way, we can outline an overall picture of the monetary discoveries associated with the site at Ocnița-Buridava, discoveries of significant importance for understanding it.